The effect of heavy-resistance core strength training on upper-body strength and power performance in national-level junior athletes–a pilot study - Saeterbakken, Atle Hole; Sandvikmoen, Tor Einar; Iversen, Erik; Bjørnsen, Thomas; Stien, Nicolay; Andersen, Vidar; Scott, Suzanne; Prieske, Olaf (Frontiers in Physiology, 2025)
IntroductionThe concept of core strength refers to the ability of the core muscles to transfer, absorb and re-direct energy, and generate force/torque while providing proximal stability for distal mobility of the limbs. The aim of the present study was to examine the effects of an 8-week heavy-resistance core strength training (HR-CST) program on upper-body strength and power performance in young athletes. The secondary aim was to examine the role of sport-specific training background (kayak sprinters vs. swimmers) and sex (males vs. females).MethodsEighteen national-level junior athletes (age: 17.1 ± 1.1 years, body height: 178 ± 7.8 cm, body mass: 70.2 ± 10.4 kg, 12 males, 6 females) competing in kayak sprint (n = 6) and swimming (n = 12) volunteered to participate. During the 8-week intervention period, half (i.e., 45 min) of the regular strength training program was replaced with HR-CST. Pre and post intervention, upper-body strength and power (i.e., maximal isokinetic stroke force [MIF] and power [MIP]) were tested by means of a maximal stroke test using a paddle ergometer. Additionally, peak (PP20) and average power (AP20) was determined in a 20-s all-out stroke test.ResultsPaired sample t-tests indicated that PP20 and AP20 were significantly improved by 12.8% (p < 0.001, ES = 0.30) and 11.9% (p < 0.001, ES = 0.28), respectively, following HR-CST. No statistical changes were observed in MIF and MIP (p > 0.05, 0.19 ≤ ES ≤ 0.63).Conclusion8 weeks of HR-CST appears to be an effective means to improve upper-body strength and power performance in national-level junior kayak sprinters and swimmers. Our results suggest that a dynamic high-intensity core strength-training is a viable option for improving their performance in a periodized pre-season program and should be considered.